2021
DOI: 10.1177/10790632211019726
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Analysis of Sexual Recidivism and Predictive Validity of the Static-99R in Men Discharged From State Hospitals Pursuant to California’s Sexually Violent Predator Act

Abstract: We examined the recidivism rates and the predictive validity of the Static-99R in 335 men who were detained or civilly committed and released from California State Hospitals pursuant to the Sexually Violent Predator (SVP) Act, and followed up for approximately 21 years from date of hospital admission. In all, 8.7% were arrested or convicted for a new sexual offense during the total follow-up ( N = 335) and 7.8% over a fixed 5-year follow-up ( n = 205). The Static-99R demonstrated small in magnitude discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…This is fairly consistent with the median age of the U.S. prison population (https://bjs.ojp.gov/content/pub/pdf/aspp9313.pdf) but is much younger than the typical SVP population. Given that the average age of patients discharged from SVP commitments is around 56 years old (e.g., Azizian et al, 2021), it is difficult to determine whether the offense patterns they previously exhibited in their younger years should be assumed to continue after discharge from their SVP commitments. Indeed, results from Bouchard and Lussier’s (2015) estimation methods suggested that risk of being reconvicted (or caught) are not equally distributed among age groups, with a risk of conviction twice as high for younger offenders.…”
Section: Discussionmentioning
confidence: 99%
“…This is fairly consistent with the median age of the U.S. prison population (https://bjs.ojp.gov/content/pub/pdf/aspp9313.pdf) but is much younger than the typical SVP population. Given that the average age of patients discharged from SVP commitments is around 56 years old (e.g., Azizian et al, 2021), it is difficult to determine whether the offense patterns they previously exhibited in their younger years should be assumed to continue after discharge from their SVP commitments. Indeed, results from Bouchard and Lussier’s (2015) estimation methods suggested that risk of being reconvicted (or caught) are not equally distributed among age groups, with a risk of conviction twice as high for younger offenders.…”
Section: Discussionmentioning
confidence: 99%
“…The study was an archival review of case files of individuals forensically hospitalized under postprison civil commitment pursuant to the Sexually Violent Predator Act (SVPA) who were later discharged to the community. We used the data set as detailed by Paden et al (2021) and Azizian et al (2022); the methods are as described within these published articles. As detailed within these prior publications (Azizian et al, 2022; Paden et al, 2021), institutional review board (IRB) approval was obtained from the California Committee Protection of Human Subjects, which serves as the IRB for all California state agencies.…”
Section: Methodsmentioning
confidence: 99%
“…We used the data set as detailed by Paden et al (2021) and Azizian et al (2022); the methods are as described within these published articles. As detailed within these prior publications (Azizian et al, 2022; Paden et al, 2021), institutional review board (IRB) approval was obtained from the California Committee Protection of Human Subjects, which serves as the IRB for all California state agencies. The study also underwent review by the California State Hospital Research Committee.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there could be varying time elapsed from the 60th birthday to the date of their annual evaluation, the judge to consider a petition, and a resulting trial can take several years (e.g. Azizian et al, 2021).…”
Section: Decision Making In Svp Proceedingsmentioning
confidence: 99%
“…For example, there could be varying time elapsed from the 60th birthday to the date of their annual evaluation, the judge to consider a petition, and a resulting trial can take several years (e.g. Azizian et al., 2021). Thus, the number of years since turning 60 may be an important factor in whether a patient has had enough time to fully pursue and proceed through the discharge processes.…”
Section: Introductionmentioning
confidence: 99%